Identification of Groundwater Aquifer Layers in Sajang Using Vertical Electrical Sounding - Syarifatul Ulfah; Arif Wijaya (Rekayasa, 2026)
Groundwater availability is an essential factor in supporting domestic activities, agriculture, and tourism development in Sajang Village, East Lombok, Indonesia. Nevertheless, scientific information regarding subsurface groundwater potential in this volcanic region remains limited. The research contribution is the evaluation of subsurface lithology and groundwater aquifer potential in Sajang using the Vertical Electrical Sounding method to support groundwater exploration planning. This research applied the Vertical Electrical Sounding (VES) technique with the Schlumberger electrode configuration at two observation points. Field measurements were processed through inversion analysis using IP2WIN software to obtain true resistivity values and interpret lithological characteristics beneath the surface. The interpretation results reveal that the subsurface structure is dominated by volcanic rocks consisting of overburden, andesite lava, and andesite breccia with generally high resistivity values. At the first sounding point, resistivity values range from 77.8 Ωm to 11 × 107 Ωm at depths reaching 150 m. Meanwhile, the second sounding point shows resistivity values between 17.2 Ωm and 44 × 105 Ωm at depths of up to 153 m. The absence of low-resistivity zones indicates that productive aquifer layers are not present within the investigated area. Consequently, groundwater drilling activities are not recommended at the measurement locations. This study provides updated hydrogeophysical information for groundwater assessment in volcanic terrains of East Lombok.